1999
DOI: 10.1101/gad.13.21.2811
|View full text |Cite
|
Sign up to set email alerts
|

A specific protein-protein interaction accounts for the in vivo substrate selectivity of Ptp3 towards the Fus3 MAP kinase

Abstract: The mitogen-activated protein kinases (MAPKs) play critical roles in many signal transduction processes. Several MAPKs have been found in Saccharomyces cerevisiae, including Fus3 in the mating pathway and Hog1 in the osmotic-stress response pathway. Cells lacking Fus3 or Hog1 activity are deficient in mating or adaptation to osmotic shock, respectively. However, constitutive activation of either Fus3 or Hog1 is lethal. Therefore, yeast cells have to tightly regulate both the activation and inactivation of Fus3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 56 publications
1
49
0
Order By: Relevance
“…Although the functional significance of these motifs remains unknown, it has been proposed that they could be involved in the association with MAPKs (41). In support of this hypothesis, the yeast tyrosine phosphatase Ptp3 has been shown to interact with the MAPK Fus3 through the CH2 domains (42). Recently, a basic motif-based docking domain, present in different types of MAPK-interacting proteins, has been shown to be involved in their association with MAPKs (43).…”
Section: Discussionmentioning
confidence: 74%
“…Although the functional significance of these motifs remains unknown, it has been proposed that they could be involved in the association with MAPKs (41). In support of this hypothesis, the yeast tyrosine phosphatase Ptp3 has been shown to interact with the MAPK Fus3 through the CH2 domains (42). Recently, a basic motif-based docking domain, present in different types of MAPK-interacting proteins, has been shown to be involved in their association with MAPKs (43).…”
Section: Discussionmentioning
confidence: 74%
“…In the yeast mating pathway, putative D-sites are also been found in Gpa1 Gα [102], the Ptp3 phosphatase [154], and the Dig1 and Dig2 transcriptional regulators [79]. Hence, D-sites appear to be portable, modular motifs that mediate the interaction of MAPKs with multiple binding partners, contributing to both signal transmission and specificity.…”
Section: Ste7 Mek and Mapk Phosphorylationmentioning
confidence: 99%
“…It remains to dissect out specific roles of these phosphatases in regulation of Slt2 and other target kinases. It has been shown that protein-protein interaction through amino-terminal noncatalytic domains of Ptp2 and Ptp3 determines their substrate specificity toward Hog1 and Fus3 (40). In addition, the localization of phosphatases could affect their specificity toward various MAPKs.…”
Section: Discussionmentioning
confidence: 99%